CONTEXTUALIZATION OF HIFZ AL-DIN IN INTER-RELIGIOUS INTERACTIONS ACCORDING TO ISLAMIC LAW: (STUDY OF QURAISH SHIHAB'S FATWAS ON MUSLIM AND NON-MUSLIM RELATIONS) - Lukman Hakim; Muhamad Risqil Azizi (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
The problem of relations between religious communities until now still has the potential to cause conflict in the midst of plurality of society. Conflicts based on religious sentiments are often based on exclusive religious understandings that tend to be segregative of 'other'. With that, coexistence between religious communities will be difficult to realize. This exclusive view is based on the emotional basis of defending religion (hifz al-din). On that basis, this paper wants to explore the concept of hifz al-din in the discourse of maqasid al-shari'ah and how it is understood in religious views and fatwas. The religious fatwas chosen as the focus in this study are the fatwas of Quraish Shihab concerning interaction between religious communities (Muslims and non-Muslims). This study concludes that the concept of hifz al-din is an evolving discourse (mutagayyirat). The understanding of hifz al-din actually leads not only to an exclusive religious view (min janib al-'adam), but also inclusive (min janib al-wujud). In addition, the so-called hifz al-din deals with the three dimensions of Islamic teaching, namely the laws of creed (ahkam 'i'tiqadiyah), the laws concerning deeds (ahkam 'amaliyah), and the norms of morality (ahkam khuluqiyyah). In Quraish Shihab's religious fatwas on Muslim and non-Muslim relations, for matters closely related to faith, the basis of hifz al-din that tends to be used is exclusive (min janib al-'adam) as in matters of the law of prayer in the church, or marriage between Muslims and non-Muslims. Whereas in matters that are not related at all to belief, such as in matters concerning financial transactions, the basis of hifz al-din used tends to be inclusive (min janib al-wujud).